2008
DOI: 10.2174/138945008784911813
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling in Renal Cancer

Abstract: About one fourth of people diagnosed with kidney cancer in 2007, are expected to die of this disease within 5 years from the date of diagnosis. Recent years have produced novel drugs, some with FDA approval, and many in clinical trials, all showing very discrete results. Failure in finding effective treatments to improve survival with drugs mainly targeting VEGF and its downstream effectors, urges to shift the drug development targets to other unexploited pathways shown to be also involved in renal cancer. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 106 publications
4
22
0
Order By: Relevance
“…The Wnt pathway is activated in a wide variety of tumors such as prostate cancer (40), renal cancer (41), ovarian cancer (42), and EC (19). Wang et al,(43) reported that progesterone inhibits Wnt signaling in the human endometrium through induction of DKK1 and FOXO1.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt pathway is activated in a wide variety of tumors such as prostate cancer (40), renal cancer (41), ovarian cancer (42), and EC (19). Wang et al,(43) reported that progesterone inhibits Wnt signaling in the human endometrium through induction of DKK1 and FOXO1.…”
Section: Discussionmentioning
confidence: 99%
“…Kurose et al (2004) reported a high incidence of DKK-3 silencing specifically in RCC, suggesting that DKKs also possess tumor suppressor activity. A recent and comprehensive review of Wnt signaling in renal cancer is available (Guillen-Ahlers, 2008). …”
Section: Key Moleculesmentioning
confidence: 99%
“…14, 15, 16, 17, 18 In CRC, adenomatous polyposis coli (APC) is the key tumour suppressor protein and is mutated in ∼80% of sporadic cancers. Moreover, germline heterozygosity of this gene leads to familial adenomatous polyposis (FAP).…”
Section: Introductionmentioning
confidence: 99%